1985
DOI: 10.1902/jop.1985.56.12.748
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Etiology and Pathogenesis of Early‐Onset Periodontitis: Cementopathia Revisited

Abstract: For more than 20 years, investigators have unanimously agreed that human periodontitis is caused by bacterial colonization of the surfaces of the teeth and their extension apically. Recently, several investigators have demonstrated that most, if not all, individuals manifesting the early-onset, aggressive forms of periodontitis have abnormalities in their peripheral blood phagocytes which can be detected as abnormal cell motility or adherence. Because of the major role of these cells, especially the neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 5 publications
0
58
0
Order By: Relevance
“…However, diseased roots support neither the attachment nor the growth of fibroblasts, and extracts of diseased cementum inhibit fibroblast growth (Fernyhough and Page, 1983;Pitaru and Melcher, 1983;Olson et al, 1985). These data, as well as other studies, indicate that cementum contributes to the repair of periodontal connective tissue and restoration of soft tissue attachment to roots affected by periodontal disease (Lindskog and Bloml6f, 1983;Page and Baab, 1985;Knox and Aukhil, 1988).…”
mentioning
confidence: 77%
“…However, diseased roots support neither the attachment nor the growth of fibroblasts, and extracts of diseased cementum inhibit fibroblast growth (Fernyhough and Page, 1983;Pitaru and Melcher, 1983;Olson et al, 1985). These data, as well as other studies, indicate that cementum contributes to the repair of periodontal connective tissue and restoration of soft tissue attachment to roots affected by periodontal disease (Lindskog and Bloml6f, 1983;Page and Baab, 1985;Knox and Aukhil, 1988).…”
mentioning
confidence: 77%
“…PgE2 production might be induced in resident joint cells after deposition of pyrophosphate crystals in joint and bone tissue (Dayer et al, 1987;Girschick et al, 1999a;Schumacher, 1995). PgE2 is a potent pain mediator and can be an effective stimulator of bone demineralization resulting in skeletal and tooth hypomineralisation, cementum hypoplasia, and premature exfoliation of the primary teeth (Bergmann and Schoutens, 1995;Girschick et al, 1999a;Kawaguchi et al, 1995;Page and Baab, 1985;Raisz, 1995;Saito et al, 1991). The clinical severity of the symptoms has been classified into clinical types according to severity and age of onset.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis can be viewed as a disturbance of the microbial ecology resulting in an increase in the number of Gram-negative and anaerobic bacteria. Case reports have described an association between HP and periodontitis (Baab et al, , 1986Page and Baab, 1985;Watanabe et al, 1993). Baab et al (1985Baab et al ( , 1986 reported the presence of putative periodontal pathogens in the subgingival microflora and elevated levels of serum antibodies to the periodontal pathogen Porphyromonas gingivalis in HP patients.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was in support of Gottlieb's (18) idea that periodontitis was associated with 'cementopathia'. Page & Baab (21) have suggested that several cases in previously published reports of early exfoliation of deciduous teeth and juvenile, prepubertal, and rapidly progressive periodontitis are in fact due to hypophosphatasia and the associated abnormalities in cementum formation. Page & Baab (21) have suggested that several cases in previously published reports of early exfoliation of deciduous teeth and juvenile, prepubertal, and rapidly progressive periodontitis are in fact due to hypophosphatasia and the associated abnormalities in cementum formation.…”
mentioning
confidence: 99%